2008
DOI: 10.1007/s00421-008-0861-0
|View full text |Cite
|
Sign up to set email alerts
|

Moderate exercise training decreases aortic superoxide production in myocardial infarcted rats

Abstract: Myocardial infarction (MI) has been associated with increases in reactive oxygen species (ROS). Exercise training (ET) has been shown to exert positive modulations on vascular function and the purpose of the present study was to investigate the effect of moderate ET on the aortic superoxide production index, NAD(P)H oxidase activity, superoxide dismutase activity and vasomotor response in MI rats. Aerobic ET was performed during 11 weeks. Myocardial infarction significantly diminished maximal exercise capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
0
13
0
4
Order By: Relevance
“…Regarding physical activity, it has been described that exercise training diminished production of reactive oxygen species in rats [30]. Moreover, another study showed an increased activity of glutathione peroxidase in erythrocytes although serum Se did not change between active and sedentary elderly subjects [31].…”
Section: Discussionmentioning
confidence: 98%
“…Regarding physical activity, it has been described that exercise training diminished production of reactive oxygen species in rats [30]. Moreover, another study showed an increased activity of glutathione peroxidase in erythrocytes although serum Se did not change between active and sedentary elderly subjects [31].…”
Section: Discussionmentioning
confidence: 98%
“…13 Accumulating evidence indicates that regular aerobic exercise restores the balance between NO production and NO inactivation by reactive oxygen species. 21,22 Therefore, it is possible that each of LTP ingestion and regular aerobic exercise increases vascular endothelial function by different physiological mechanisms, and this may be the reason as to why the effects of LTP ingestion and regular aerobic exercise appear to be additive.…”
Section: Lactotripeptides Exercise and Endothelial Functionmentioning
confidence: 96%
“…In animal and human studies, exercise training programs resulted in an increased vascular expression of antioxidative enzymes, such as SOD, catalase, and glutathione peroxidase [133][134][135] and a reduced expression of ROS-generating enzymes such as nicotinamide adenine dinucleotide phosphate (NAD[P]H) oxidase and xanthine oxidase. 94,136 Nicotinamide adenine dinucleotide phosphate (NAD[P]H) oxidase expression and activity are regulated mainly by the dominant influence of angiotensin II type 1 receptor activation by inducing a rapid rac1 translocation to the cell membrane. 137 In addition, a 4-week exercise training program in patients with coronary artery disease resulted in a significantly lower expression of angiotensin II type 1 receptor compared with a sedentary control group.…”
Section: No Generation In the Endotheliummentioning
confidence: 99%